The use of therapeutic plasma exchange as adjunctive therapy in the treatment of coronavirus disease 2019: A critical appraisal of the current evidence. Issue 3 (12th February 2021) - Lu, Wen; Kelley, Walter; Fang, Deanna C.; Joshi, Sarita; Kim, Young; Paroder, Monika; Tanhehco, Yvette; Tran, Minh‐Ha; Pham, Huy P.
Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has led to a major pandemic. While vaccine development moves forward, optimal treatment continues to be explored. Efforts include an ever‐expanding number of clinical trials along with newly proposed experimental and off‐label investigational therapies; one of which is therapeutic plasma exchange (TPE). There have been a number of publications on TPE use as adjunctive therapy for coronavirus disease 2019 (COVID‐19), but no prospective randomized controlled trials (RCTs) have been completed. This article critically appraises the current available evidence on TPE as a treatment modality for SARS‐CoV‐2 infection.